Оценка влияния погрешности на решение обратной задачи индукционного каротажа - Миронцов, Н.Л. (Доповіді НАН України, 2011)
Розглянуто питання впливу похибки індукційного каротажу на величину похибки розв'язку оберненої задачі для пластів обмеженої потужності. Показано, що розв'язок, представлений рядом Фур'є обмеженої кількості членів, стійкий для дозволених на практиці величин похибки. Висновки грунтуються на моделюванні індукційного каротажу різноманітними зондами в умовах Дніпровсько-Донецької западини та Західного Сибіру. The question of an influence of errors of the induction logging on the error of the inverse problem solution for strata with restricted thicknesses is considered. It is shown that the solution represented in the form of a Fourier series with limited number of terms is stable for errors allowable in practice. The conclusions are based on the modeling of a logging executed with various probes under conditions of the Dnieper-Donets depression and the Western Siberia.